Rancang Bangun Purwarupa Alat Penghasil Riak Gelombang Air: Pengujian Kinerja Purwarupa Penghasil Gelombang Air - Renaldi, Rendi; Ilyas Hadikusuma, Mohd; Mardianto, Eko; Rusyda Saufa, Nanda; Ridhwan Sufandi, Muhammad (Electrical Network Systems and Sources, 2024)
This research aims to develop a prototype of a laboratory-scale wave generator to explore the potential of river wave energy, which has mostly been focused on marine energy due to its significant potential. The device consists of a container measuring 100x22x30 cm, using a servo motor to generate water ripples and an ultrasonic sensor to detect ripple height. Two propulsion methods are employed: simultaneous and alternating, with more varied ripple patterns observed in the alternating method. Changes in the servo motor’s angle produce three thrust levels with different wave heights: slow (1-2 cm), moderate (2.5-3 cm), and strong (3 cm). The findings highlight the renewable energy potential of river wave energy, which can be harnessed sustainably, reducing carbon emissions, dependency on fossil fuels, while enhancing energy security and job creation.